Change Detection on Land Use and Land Cover Changes in the Wetland Ecosystem of the Niger Delta Region. - Wali, Elekwachi; Kika, Helen. A; Gbuvboro, Anthonia Ejiroghene; Daniel, DorkaNwidag. (Journal of Research in Environmental and Earth Sciences, 2025)
LULC changes have been upsetting marine and inland ecosystems, including wetlands, leading to serious destruction of wetlands global. The study examines change detection on land use and land cover changes in the wetland ecosystem of the Niger Delta Region, Nigeria from 1986 - 2016.This study adopted a cross-sectional research design method, both primary and secondary data sources were activated in the study while data set includes a notable period of four epoch years land sat images of 1986, 1996, 2006, and 2016, LandSat5Thematic Mapper (TM,) Landsat7Enhanced Thematic Mapper (ETM +), Thermal Infrared Sensor (TIRS) and Landsa8 Operational Land Imager (OLI). The data analysis was carried out through ArcGIS 10.6 environment, descriptive and inferential statistics, Cohen’s Kappa statistic were employed in the study. A total area of 25053.93 (km2) was delineated in the study area and the overall accuracy assessment using kappa statistics shows that from 1986-2016 was 86.06% (0.85 kappa coefficient). The entire results show that land use type has changed over the four epoch years as thus: fallow land covered around 18.317%,13.61%,12.231%, 25.928 %, respectively; built-up areas covered 5.449 %, 14.639 %, 15.795%, and 16.792%, across the study years; natural-vegetation covered around 32.905%, 32.404 %, 30.161%, and 28.156 %; waterbodies covered6.244 %, 6.421 %, 8.051 %, 8.059 %, and wetland covered 37.085%, 33.926%, 33.762 %, and 21.065 %, respectively. These observable trends occur as a result of overall changes in land cover patterns and the conversion of natural land to human-modified landscapes. Conclusively this study will enable planners, conservationist, environmentalist and policymakers to formulate appropriate strategies for the long-term conservation of these vital ecosystems. In furtherance this study demonstrates that GIS and Remote Sensing techniques is a comprehensive and Eco-friendly tool for land monitoring, sustainably capacity building for land inventory and collective understanding of wetland ecosystem and land use and land cover dynamics.
Keywords: Change Detection; Landuse/ Landcover; Wetland; Ecosystem; Niger Delta.